Design of Track Transitions: Research Results Digest 79. (Transportation Research Board, 2006)
"This digest summarizes the results of TCRP Project D-7/Task 15. The digest was prepared by the Transportation Technology Center, Inc. ... David Read and Dingqing Li served as principal authors."
Keywords: Railroad tracks -- Design and construction.; Ballast (Railroads); elektronické knihy; electronic books